The South Bank Show: Werner Herzog - Bond, Jack; Sinclair, Peter (The Werner Herzog Collection, 2014)
Back in 1982, ITV focused an entire episode of "The South Bank Show" to Werner Herzog, and as usual, you should probably watch it. Across 60 minutes, it jumps around with the director, highlighting his films to date, talking with him about his work with Klaus Kinski, showing him reading dramatically on a train and … talking about soccer. In fact, you’ll see Herzog play soccer, as he talks about his fave English footballer Glenn Hoddle. [www.indiewire.com]